2021
DOI: 10.3390/microorganisms9020323
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length Genome and Partial Viral Genes Phylogenetic and Geographical Analysis of Dengue Serotype 3 Isolates

Abstract: Dengue fever is among the most common vector-borne diseases. Dengue virus (DENV), responsible for dengue fever as well as dengue hemorrhagic fever, belongs to the genus flavivirus and family Flaviviridae. Flaviviruses infect various vertebrate species and arthropods and are also responsible for diseases in birds, wild animals, and primates. DENV consists of a single-stranded, positive-sense RNA genome ~11 kb in size. Complete genome and partial gene sequences of geographically distinct DENV-3 strains were retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
(31 reference statements)
0
3
0
1
Order By: Relevance
“…Our analysis of DENV-1–4 amino acid variants revealed that NS5 was the most frequently mutated gene, followed by NS3 and E. The NS5 region encompasses the polymerase region that is highly conserved between serotypes and plays a key role in maintaining viral fitness and replication capacity [ 43 ]. Most of the variants of DENV-1, DENV-2, and DENV-4 were non-synonymous, while DENV-3 variants were predominantly due to synonymous changes in the NS5, NS3, and E proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of DENV-1–4 amino acid variants revealed that NS5 was the most frequently mutated gene, followed by NS3 and E. The NS5 region encompasses the polymerase region that is highly conserved between serotypes and plays a key role in maintaining viral fitness and replication capacity [ 43 ]. Most of the variants of DENV-1, DENV-2, and DENV-4 were non-synonymous, while DENV-3 variants were predominantly due to synonymous changes in the NS5, NS3, and E proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of this study is that the research area is not wide because this is a preliminary study to build a vulnerability index of an area and spatial distribution to dengue [38], [43]. One of the factors that influence dengue cases is environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have focused on the sequence analyses of viral individual genes or a subset of those genes, with the envelope (E) gene and C-prM region are the most frequently selected targets for DENV phylogenetic investigations and genotyping [36,38,49,50]. However, a recent comparative analysis of viral mutations and evolution demonstrated signi cant differences when DENV wholegenome sequences were analyzed instead of individual genes [51]. Therefore, additional studies with whole DENV genome sequencing might provide critical information about the genetic relation between DENV isolates circulating in Jazan region and variants circulating in other regions.…”
Section: Discussionmentioning
confidence: 99%